ANALYSIS OF HEAT TRANSFER OF INFANT WARMER - Nofrizalidris Darlis; Nurulnatisya Ahmad; Mohammad Hatta Ramlee; Ab Aziz Mohd Yusof; Kamariah Md Isa; Muhammadu Masin Muhammadu, (Applications of Computational Fluid Dynamics in Mechanical Engineering (Series 4), 2025)
An infant warmer is an overhead heating device used to help infants regulate their body heat to achieve their normal body temperature. However, problems may arise in obtaining the correct heat settings. The objective of this study is to determine the most appropriate operating conditions of such units. A combined analysis of heat transfer from the heat source and the influence of the surrounding environment temperature is performed to calculate the temperature distribution for the infant warmer. A simulation application is used to recreate the design and run the simulations according to the boundary conditions as a guideline. The results for a single heat source show a very non-uniform temperature distribution. On the other hand, the results for the double heat source show a very uniform heat temperature distribution. Based on the observations, it is recommended that a dual heat source be used for an infant warmer for more favourable results.Keywords: Infant warmer, Heat transfer, CFD